RP-HPLC Analytical Method Development and Validation of Avibactam and Aztreonam - Gangu Sreelatha,; Nandini Kolli,; Arunabha Mallik, (Asian Journal of Pharmaceutical Research and Development, 2026)
A simple, rapid, precise, sensitive, and reproducible reverse phase high performance liquid chromatography (RP-HPLC) method has been developed for the quantitative analysis of Avibactam and Aztreonamin pharmaceutical dosage form. Chromatographic separation of Avibactam and Aztreonamwas achieved on Waters Alliance-e2695by using Luna Phenyl Hexyl (250x 4.6mm, 5µ) column and the mobile phase containing Acetonitrile: 0.1% Formic acid in the ratio of 20:80% v/v. The flow rate was 1.0 ml/min; detection was carried out by absorption at 250nm using a photodiode array detector at ambient temperature. The number of theoretical plates and tailing factors for Avibactam and Aztreonam were NLT 2000 and should not be more than 2 respectively. % Relative standard deviation of peak areas of all measurements always less than 2.0. The proposed method was validated according to ICH guidelines. The method was found to be simple, economical, suitable, precise, accurate & robust method for quantitative analysis of Avibactam and Aztreonam study of its stability.